"Bajta ni drugega kakor kotišče otrok, nezadovoljnosti in nesreče" - Ratej, Mateja (Časopis za zgodovino in narodopisje, 2023)
For future generations to gain insight into the invisible and utterly discarded lives of those who were often invisible and ignored by society such as maids, crofters, cottagers, innkeepers, lodgers or winemaker’s wives, their paths had to be crossed by a crime that has driven police investigators and judicial authorities to investigate the dilapidated and abandoned details of their daily lives. However, it is very rare to come across any records of the lives of thousands of other women from the social fringes of inter-war Slovenian society who never compromised their anonymity by an excess of behaviour or an event. During the World Wars, the lives of farm workers could and often did end without any criminal record. The author of this article analysing the problem of great social stratification as the main social antagonism during the interwar period concludes that even the most talented members of the peasant proletariat were unable to progress beyond the status of a worker, cook, washerwoman or maid due to social determinism. As a result, some of them sought to raise their social status by committing crimes.
Keywords: 1918-1941; družbeno nasilje; kočarji; nasilje; slovenska zgodovina; socialni položaj; Štajerska; terminologija; ženske